Consensus paper of the WFSBP task force on biological markers: Biological markers for alcoholism. (December 2013) - Hashimoto, Eri; Riederer, Peter Franz; Hesselbrock, Victor M.; Hesselbrock, Michie N.; Mann, Karl; Ukai, Wataru; Sohma, Hitoshi; Thibaut, Florence; Schuckit, Marc A.; Saito, Toshikazu
Abstract Objectives. This article presents an overview of the current literature on biological markers for alcoholism, including markers associated with the pharmacological effects of alcohol and markers related to the clinical course and treatment of alcohol-related problems. Many of these studies are well known, while other studies cited are new and still being evaluated. Methods. In this paper we first describe known biomarkers of alcohol-related disorders, review their features and the problems involved in their use. We then consider future developments on biomarkers and their possible impact on the field. Results. More recent findings cited include the work on type 7 adenylcyclase (AC) polymorphism and its lower expression levels in female alcoholics. Neuroimaging studies involving biomarkers have also reported brain volume reductions of gray and white matter, including amygdala and subcortical regions in alcoholic patients, while a high association between the copy number variations (CNVs) in 6q14.1/5q13.2 and alcohol dependence has more recently been identified in genetic studies. Conclusions. In addition to their possible importance for diagnosis, biomarkers may have utility for predicting prognosis, progression of the disorder, the development of new treatments, and monitoring treatment effects. Although such findings should be verified in independent studies, the search for new biomarkers is continuing. Several potential candidate biomarkers have been found recently in blood, imaging, and genetic studies with encouraging results.